BrdU Pulse Labelling In Vivo to Characterise Cell Proliferation during Regeneration and Repair following Injury to the Airway Wall in Sheep - Yahaya, B.; McLachlan, G.; Collie, D. D. S. (Hindawi Publishing Corporation, 2013)
The response of S-phase cells labelled with bromodeoxyuridine (BrdU) in sheep airways undergoing repair in response to endobronchial brush biopsy was investigated in this study. Separate sites within the airway tree of anaesthetised sheep were biopsied at intervals prior to pulse labelling with BrdU, which was administered one hour prior to euthanasia. Both brushed and spatially disparate unbrushed (control) sites were carefully mapped, dissected, and processed to facilitate histological analysis of BrdU labelling. Our study indicated that the number and location of BrdU-labelled cells varied according to the age of the repairing injury. There was little evidence of cell proliferation in either control airway tissues or airway tissues examined six hours after injury. However, by days 1 and 3, BrdU-labelled cells were increased in number in the airway wall, both at the damaged site and in the regions flanking either side of the injury. Thereafter, cell proliferative activity largely declined by day 7 after injury, when consistent evidence of remodelling in the airway wall could be appreciated. This study successfully demonstrated the effectiveness of in vivo pulse labelling in tracking cell proliferation during repair which has a potential value in exploring the therapeutic utility of stem cell approaches in relevant lung disease models.